La Parade – Notre Histoire - Baier, Lionel (Switzerland : Cine Manufacture CMS SA ; Television Suisse Romande, 2001)
In July 2001, in Sion, a Catholic stronghold and capital of the ruggedly mountainous Swiss canton of Valais, a group of six women and a man, led by Marianne Bruchez, dared to organise the first gay parade ever held in this small provincial town. The community officials refused to issue the required permit for the parade, local protesters published a slanderous full-page article in the local newspaper. Marianne Bruchez, a young thirty-year-old woman with no previous experience as a gay activist, suddenly found herself making front-page news in Swiss newspapers, and being forced to accept high-profile media visibility of the worst sort.
Duration: 01:18:00
Keywords: Documentary films